From burrows to spotlight: first description of the female of Eresus lavrosii Mcheidze, 1997 (Araneae, Eresidae), with notes on the natural history - Armen Seropian; Natalia Bulbulashvili; Giorgi Makharadze; Gábor Kovács (Caucasiana)
Eresidae (velvet spiders) is a relatively small family of spiders, most-diversified in the African continent. The present study provides the first description of the female of Eresus lavrosii Mcheidze, 1997, which has remained undiscovered for over two decades. We also briefly review the species’ history and add knowledge of its ecology, biology, and distribution. Diagnostic drawings and digital photographs of female and male copulatory organs, alongside COI barcoding results, photographs of live and preserved specimens, and of microhabitat are also presented.